2020
DOI: 10.1111/brv.12591
|View full text |Cite
|
Sign up to set email alerts
|

Mixed company: a framework for understanding the composition and organization of mixed‐species animal groups

Abstract: Mixed‐species animal groups (MSGs) are widely acknowledged to increase predator avoidance and foraging efficiency, among other benefits, and thereby increase participants' fitness. Diversity in MSG composition ranges from two to 70 species of very similar or completely different phenotypes. Yet consistency in organization is also observable in that one or a few species usually have disproportionate importance for MSG formation and/or maintenance. We propose a two‐dimensional framework for understanding this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 216 publications
4
135
0
Order By: Relevance
“…The flocks characterized here appear to be structured largely by complementary rather than supplemental benefits, sensu Goodale et al. (2020). We do not note any examples of convergence in plumage or call that might suggest the flocks were shaped by supplementary benefits.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The flocks characterized here appear to be structured largely by complementary rather than supplemental benefits, sensu Goodale et al. (2020). We do not note any examples of convergence in plumage or call that might suggest the flocks were shaped by supplementary benefits.…”
Section: Discussionmentioning
confidence: 93%
“…In New Guinea, mixed‐species flocks are found that appear to have both elements of the supplementary and complementary models of Goodale et al. (2020). Flocks centered around the Papuan babbler ( Garritornis isidorei ), for example, include constituent species that mimic the babbler's plumage and call (Bell, 1983; Diamond, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the above examples suggest, social information may originate not only from conspecifics, heterospecific individuals are also likely to be an important, and for a long time overlooked, source of social information (Seppänen et al, 2007;Webster and Laland, 2017;Sridhar and Guttal, 2018). Using social information produced by heterospecifics might be preferable when territoriality or competition among conspecific individuals limit the frequency of direct interactions (Goodale et al, 2020); in line with that, foraging in mixed-species groups has been predicted to be more beneficial under several ecological scenarios than foraging in single species groups (Gil et al, 2017). Nongrouping animals may encounter heterospecific social cues more frequently than cues originating from conspecifics; on the other hand, such cues can be less reliable or relevant as well.…”
Section: Exploitation Of Social Cues In Non-grouping Animalsmentioning
confidence: 99%
“…similar physiological characteristics and motivation assemble in aggregations and display some temporary synchrony in their patterns of activity (e.g., some fish shoals or locust swarms), while in other organisms, like eusocial hymenopterans, they form highly structured, and stable societies (Ward and Webster, 2016). Animals often aggregate with heterospecifics and create mixedspecies groups as well, especially when they share resources or are subject to the same threats (Goodale et al, 2017(Goodale et al, , 2020. Because of the apparent diversity in animal grouping behavior, however, the dichotomous categorization of animals into group-living and solitary species can be misleading.…”
mentioning
confidence: 99%